Bowel Preparations Administered the Morning of Colonoscopy Provide Similar Efficacy to a Split Dose Regimen: A Meta Analysis. Issue 10 (November 2018) - Avalos, Danny J.; Castro, Fernando J.; Zuckerman, Marc J.; Keihanian, Tara; Berry, Andrew C.; Nutter, Benjamin; Sussman, Daniel A.
Abstract : Background: Comparative efficacy of same-day bowel preparations for colonoscopy remains unclear. Aims: A meta-analysis of randomized controlled trials comparing the efficacy of same-day versus split dose bowel preparations for colonoscopy. Methods: A systematic search was conducted in MEDLINE, clinicaltrials.gov, Cochrane Registry, EMBASE, SCOPUS, Web of Science and CINAHL. Studies were gathered using keywords: "morning preparation", "morning bowel preparation", "same day bowel preparation", and "colonoscopy." Pooled estimates of bowel preparation quality were analyzed among studies with categorical and continuous outcomes according to relative risk (RR) or mean difference (MD). A random effects model was chosen a priori for all analyses. Results: A total of 1216 studies were retrieved with 15 trials meeting inclusion criteria. The categorical outcome of high quality bowel preparation for any same-day bowel preparation versus any split preparation was no different with a RR 0.95 [0.90;1.00] ( P =0.62). Adenoma detection rate (ADR) was not different between groups, RR 0.97 [0.79;1.20] ( P =0.81). Willingness to repeat and tolerability did not differ (RR 1.14 [0.96, 1.36] ( P =0.14) and RR 1.00 [0.96;1.04] ( P =0.98), respectively. Adverse events were similar except for bloating, which was less frequent among the same-day preparation group, RR 0.68 [0.40;0.94] ( P =0.02). Conclusion: No clinically significant differences were noted among recipients of same day or split dose regimens. Adenoma detection rate, willingness to repeat and tolerability were similar, but bloating and interference with sleep favored the same-day preparations. Given lack of clinical differences, patient preference should dictate timing of colonoscopy preparation. Abstract : Supplemental Digital Content is available in the text.